2016
DOI: 10.1007/s10661-016-5259-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality using DEA and AHP: a case study in the Sereflikochisar region in Turkey

Abstract: This study investigated the spatial distribution of groundwater quality in Sereflikochisar Basin, in the Central Anatolian region of Turkey using different hydrochemical, statistical, and geostatistical methods. A total of 51 groundwater samples were collected from the observation wells in the study area to evaluate the characteristics of the groundwater quality. As a relatively simple and practical method, a groundwater quality index (GWQI) was developed to evaluate the overall groundwater quality. In this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…One of the most influential elements regarding environment concerns all over the world is the anthropogenic distribution, e.g., sewage discharge into the river, reclamation process of the land, and climate change due to atmospheric deposition effects [1]. In the recent years, much attention is paid by various researchers in assessing the quality of surface water because of its direct connection not only with human beings but also with other species [2]. e major factors affecting the quality of river water usually are morphology of the basin and regional atmosphere along with climate change, and both natural and anthropogenic effects are responsible for governing these effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most influential elements regarding environment concerns all over the world is the anthropogenic distribution, e.g., sewage discharge into the river, reclamation process of the land, and climate change due to atmospheric deposition effects [1]. In the recent years, much attention is paid by various researchers in assessing the quality of surface water because of its direct connection not only with human beings but also with other species [2]. e major factors affecting the quality of river water usually are morphology of the basin and regional atmosphere along with climate change, and both natural and anthropogenic effects are responsible for governing these effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, various geochemical methods have been successfully used to assess groundwater quality in world and Iran (e.g., Pazand and Javanshir 2014;Barzegar et al 2016;Fijani et al 2016;Kavurmac and Ustun 2016). Additionally, numerous recent studies have focused on analyzing the natural concentrations of several ions and metals in groundwater, to isolate anthropogenic and natural sources that affect groundwater quality, and establish interactions that take place within the aquifer (e.g., Aghazadeh and Mogaddam 2010;Jacintha et al 2016;Ehya and Marbouti 2016;Sethy et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a steady-state increase in its usage since its introduction, due to its ease of application. A large body of research concerning with AHP applications in different disciplines can be found in literature including, but not limited to, wastewater services [7], new product development [10], Internet finance [9], sustainable and renewable energy [24,25], water resources management [5,6], agriculture [26], health [8], nuclear power [27], climate change [28], and presidential elections [29].…”
Section: Analytic Hierarchy Processmentioning
confidence: 99%
“…On the one hand, the analytic hierarchy process (AHP) proposed in [4] introduces relative priority levels and cardinal preferences. A broad range of recent AHP applications can be found in many different disciplines dealing with environmental problems [5][6][7], health [8], finance [9], and product development [10].…”
Section: Introductionmentioning
confidence: 99%